ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE PADA PERUM PERHUTANI KBM-IK GRESIK SESUAI PERATURAN MENTERI NEGARA BUMN NO: PER-01/MBU/2011 - RACHMAWATI, DYAMUSTIKA (Jurnal Akuntansi AKUNESA, 2013)
To improve the performance of BUMN comprehensively and optimal then theGovernment needs to make improvements to corporate governance byimplementing Good Corporate Governance (GCG). Writing a journal purpose isaimed at implementation of the GCG on Perum Perhutani KBM-IK Gresik inaccordance with Peraturan Menteri Negara BUMN No: PER-01/MBU/2011.Research methods used are descriptive, data capture techniques used areinterviews, observation, and library study with primary data and secondary dataused for analysis. The application of GCG on Perhutani KBM-IK Gresik not goodenough because only meet the 69.23 % Peraturan Menteri Negara BUMN No:PER-01/MBU/2001Keywords: Peraturan Menteri Negara BUMN, Good Corporate Governance,Perum Perhutani